THE DIMINUTION OF TARIFF OF INTERNATIONAL TRADE TOWARDS INEQUALITY ON SOUTHEAST ASIA COUNTRIES (2007-2014) - Sudrajat, Yahya; Windiani, Reni; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
In order to implement blueprint of ASEAN Economic Community (AEC),Southeast Asia countries have been gradually doing the diminution tariff ofinternational trade since 2007. This effort has been implicating thedecreasing of each Southeast Asia countries’ GDP. Yet, this decreasing hasalso been followed by the augmentation of gini coefficients of each SoutheastAsia countries during the same time periods. Therefore, hypothesis of thisresearch is there is significant influence between the decreasing tariff ofinternational trade towards the increasing of gini coefficient in the countriesof Southeast Asia. Hence, this research had been concerned to seek ananswer of how the significance of diminution of tariff of international tradetowards the augmentation of Southeast Asia countries’ gini coefficient.